Preparation and Characterization of Fe2O3 from Iron Sand of the Coastal Sea of Cidaun Beach-South Cianjur (Indonesia) using the Co-precipitation Method - Endah Puspita; Masno Ginting; Ramlan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
The synthesis and characterization of Fe2O3 from Iron Sand of the coastal sea of Cidaun Beach - South Cianjur using the coprecipitation method has been carried out. The purpose of this research was to identify the crystal structure, magnetic mineral content, and magnetic properties of iron sands. The characterizations used in this research are X-Ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX) and Vibrating Sample Magnetometer (VSM). Based on the XRD results, it shows that the iron sand sample produces multi-phases, namely hematite (????-Fe2O3), maghemite (????-Fe2O3) and ilmenite (FeTiO3). SEM-EDX results indicate that the iron sand samples have an average particle size of 12.396 ????m. VSM results indicate that the iron sand sample is soft magnetic (ferrimagnetic) with saturation, remanence and coercivity values of 47 emu/g, 1.53 emu/g and 102.97 Oe, respectively.